2022
DOI: 10.5713/ab.22.0104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium source and level on the physiological response, reproductive performance, serum Se level and milk composition in gestating sows

Abstract: Objective: This study was conducted to evaluate the effects of selenium (Se) source and level on the physiological response, reproductive performance, serum Se level, and milk composition in gestating sows.Methods: A total of 54 multiparous sows (Yorkshire×Landrace) with average body weight (BW), backfat thickness (BF), and parity were assigned to one of five treatments with 10 or 11 sows per treatment using a 2×2 factorial arrangement with one additional treatment in a completely randomized design. Inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…It may be demonstrated that dietary Se levels did not affect milk Se content during the short-term lactation period around one reproductive cycle. Moreover, a report by Jin et al [ 29 ] also proved that despite Se source, dietary Se level could affect milk Se concentration linearly when sows were fed different Se levels (0 ppm, 0.3 ppm, 0.5 ppm) during gestation (long-term period).…”
Section: Discussionmentioning
confidence: 96%
“…It may be demonstrated that dietary Se levels did not affect milk Se content during the short-term lactation period around one reproductive cycle. Moreover, a report by Jin et al [ 29 ] also proved that despite Se source, dietary Se level could affect milk Se concentration linearly when sows were fed different Se levels (0 ppm, 0.3 ppm, 0.5 ppm) during gestation (long-term period).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies showed that when Se was supplied in an organic instead of inorganic form in a sow diet during gestation and lactation, it could improve the reproductive performance and the Se and redox status in the serum, milk, and offspring [13,18,19]. However, other studies have reported that different dietary Se sources or levels when fed during gestation and lactation had no effect on the reproductive performance, including lactation feed intakes, parturition performance, and litter performances of sows [15,16,20].…”
Section: Introductionmentioning
confidence: 99%